Quality of life in patients with proton‐treated pediatric medulloblastoma: Results of a prospective assessment with 5‐year follow‐up. Issue 16 (15th June 2018) - Kamran, Sophia C.; Goldberg, Saveli I.; Kuhlthau, Karen A.; Lawell, Miranda P.; Weyman, Elizabeth A.; Gallotto, Sara L.; Hess, Clayton B.; Huang, Mary S.; Friedmann, Alison M.; Abrams, Annah N.; MacDonald, Shannon M.; Pulsifer, Margaret B.; et al.
Abstract : BACKGROUND: To the authors' knowledge, health‐related quality of life (HRQOL) outcomes are not well described in patients with medulloblastoma. The use of proton radiotherapy (RT) may translate into an improved HRQOL. In the current study, the authors report long‐term HRQOL in patients with proton‐treated pediatric medulloblastoma. METHODS: The current study was a prospective cohort HRQOL study of patients with medulloblastoma who were treated with proton RT and enrolled between August 5, 2002, and October 8, 2015. Both child report and parent‐proxy report Pediatric Quality of Life Inventory (PedsQL) surveys were collected at baseline during RT and annually thereafter (score range on surveys of 0‐100, with higher scores indicating better HRQOL). Patients were dichotomized by clinical/treatment variables and subgroups were compared. Mixed‐model analysis was performed to determine the longitudinal trajectory of PedsQL scores. The Student t test was used to compare long‐term HRQOL measures with published means from a healthy child population. RESULTS: Survey data were evaluable for 116 patients with a median follow‐up of 5 years (range, 1‐10.6 years); the median age at the time of diagnosis was 7.6 years (range, 2.1‐18.1 years). At baseline, children reported a total core score (TCS) of 65.9, which increased by 1.8 points annually ( P <.001); parents reported a TCS of 59.1, which increased by 2.0 points annually. Posterior fossa syndrome adversely affected baseline scores, but these scores significantly improved with time. At the time of last follow‐up, children reported a TCS of 76.3, which was 3.3 points lower than that of healthy children ( P  = .09); parents reported a TCS of 69, which was 11.9 points lower than that of parents of healthy children ( P <.001). Increased follow‐up time from diagnosis correlated with improved HRQOL scores. CONCLUSIONS: HRQOL scores appear to increase over time after treatment in children treated with proton RT for medulloblastoma but remain lower compared with those of parent‐proxy reports as well as published means from a healthy normative sample of children. Additional follow‐up may translate into continued improvements in HRQOL. Cancer 2018 . © 2018 American Cancer Society . Abstract : In this large prospective cohort study of health‐related quality of life (HRQOL) outcomes in patients with proton‐treated medulloblastoma, HRQOL scores appear to improve with time, and increasing time from treatment is associated with greater gains in HRQOL. The results of the current study can serve as a benchmark comparison with studies using photon radiotherapy for contemporary comparative effectiveness analyses.